The Practice of Interfaith Tolerance Values in Schools - Rahmah Dalilah; Rukman Zeed Hamdy; A., Ibrahim Nur (Lembaga Kajian dan Pengembangan Sumberdaya Manusia, 2022)
This research explores the tolerance practices teachers and students in schools apply. It aims to analyze the tolerance practices by teachers and students in daily life in a pluralist school environment and find out how to resolve conflicts in pluralist schools. The research uses the qualitative method. The used approach is the sociology of religion with the emic-ethical method. The data collection techniques are observation and interviews. The results show: first, tolerance has taught positive values to respect people with different backgrounds. Second, various religious activities can bring out attitudes and values of tolerance between teachers and students. Third, for any problems, there must be a mediator to intervene and resolve the problems that occur so that conflicts can be resolved properly and back to upholding a pluralist attitude.